Pendampingan Peningkatan Kualitas Produksi dan Legalitas Produk UMKM Dimsum Eat’eung di Kecamatan Cileunyi - Ratna Sari Listyaningrum; Reza Fikri Alfatah; Mae Amelianawati; Zahra Khairunnisa; Fahira Shinta Arelly (Warta LPM, 2024)
According to BPOM data, only around 6,000 processed food sector MSMEs are registered, out of a total of around 10,000 businesses. This makes improving the quality and legality of products crucial, considering that many MSMEs have not been able to meet applicable food safety standards, thus limiting their access to a wider market. The target of this activity is the Eat'eung MSME located in Cileunyi with dimsum as its main product. This activity aims to empower the productive economy (Eat'eung MSME) by increasing the knowledge and skills they have in the production aspect including coaching on good food production methods and product legality. The methods used are mentoring and empowerment. There are several stages of activity including problem identification, program planning, program implementation, monitoring and evaluation, as well as dissemination and sustainability. From the results of the situation analysis, the solution is focused on coaching production layout, providing production tools, mentoring in managing CPPOB certificates and halal certificates, improving packaging labels and managing Brand IPR. The output of the activity shows that after the program there was an increase in Dimsum Eat’eung’s knowledge and skills in aspects of production layout, CPPOB and halal certificate management flow, Trademark IPR registration flow, and food packaging in accordance with regulations. In addition, there was a significant increase in various operational sub-aspects of partners that support the fulfillment of CPPOB, such as production equipment (50%), hygiene and sanitation maintenance (15%), storage (29%), and labeling (50%). The assets owned also increased, in the form of production equipment including freezers, food processors, vacuum sealers, and stainless steel tables. The follow-up plan for this program includes continuing to assist in the progress of CPPOB certification registration, halal certification, brands, and industrial design.